2016
DOI: 10.1186/s12885-016-2899-4
|View full text |Cite|
|
Sign up to set email alerts
|

A systematic comparison of copy number alterations in four types of female cancer

Abstract: BackgroundDetection and localization of genomic alterations and breakpoints are crucial in cancer research. The purpose of this study was to investigate, in a methodological and biological perspective, different female, hormone-dependent cancers to identify common and diverse DNA aberrations, genes, and pathways.MethodsIn this work, we analyzed tissue samples from patients with breast (n = 112), ovarian (n = 74), endometrial (n = 84), or cervical (n = 76) cancer. To identify genomic aberrations, the Circular B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 77 publications
0
12
0
1
Order By: Relevance
“…m6A RNA modi cation affects tumor proliferation [16], differentiation, tumorigenesis, invasion [17], and metastasis [18] by regulating proto-oncogenes and tumor suppressor genes. Similarly, CNVs play a crucial role in the occurrence, development, and outcome of several cancers, such as lung, endometrial, prostate, and gastric cancers [19][20][21][22]. However, the role of m6A methylation modi cation and CNVs in THCA is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…m6A RNA modi cation affects tumor proliferation [16], differentiation, tumorigenesis, invasion [17], and metastasis [18] by regulating proto-oncogenes and tumor suppressor genes. Similarly, CNVs play a crucial role in the occurrence, development, and outcome of several cancers, such as lung, endometrial, prostate, and gastric cancers [19][20][21][22]. However, the role of m6A methylation modi cation and CNVs in THCA is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на тот факт, что опухоли молочной железы имеют высокую степень внутриопухолевой гетерогенности, для них определены наиболее часто встречающиеся хромосомные аберрации. При РМЖ (в том числе и по данным TCGA) высокую частоту встречаемости имеют CNA в 1q, 8q, 8p, 11q, 13q, 16q, 17q и 20q регионах [4][5][6].…”
Section: __________________________unclassified
“…In the past, CGH was applied for analysis of tumor tissues, but many studies have suggested that data from primary tumors alone is insufficient. Array CGH, which exploits ordered arrays of genomic DNA sequences, is widely used for analysis of CTCs, including identification of genomic alterations which include insertion/deletion, singlenucleotide variations, copy number variations (CNVs) [72] ; identification of candidate oncogenes or tumor suppressors; identification of novel biomarkers involved in metastasis, cancer progression and therapy response; and identification of subgroups of CTCs [73] . High-throughput NGS is another strong technology to analyze heterogeneity of CTCs and reveal the mechanisms of metastasis, which might be the Achilles' heel in disease progression.…”
Section: Gene Analysis Of Ctcsmentioning
confidence: 99%